Identiﬁcation of functional residues essential for dehalogenation by the non-stereospeciﬁc a-haloalkanoic acid dehalogenase from Rhizobium sp. RC1 - Abdul Hamid, Azzmer Azzar; Tengku Abdul Hamid, Tengku Haziyamin; Abdul Wahab, Roswanira; Huyop, Fahrul Zaman (Wiley-VCH Verlag, 2013)

(untitled)
The non-stereospeciﬁc a-haloalkanoic acid dehalogenase DehE from Rhizobium sp. RC1 catalyzes the removal of the halide from a-haloalkanoic acid D,L-stereoisomers and, by doing so, converts themintohydroxyalkanoicacid L,D-stereoisomers,respectively.DehEhasbeenextensivelystudied to determine its potential to act as a bioremediation agent, but its structure/function relationship hasnotbeencharacterized.Forthisstudy,weexploredthefunctionalrelevanceofseveralputative active-site amino acids by site-speciﬁc mutagenesis. Ten active-site residues were mutated individually, and the dehalogenase activity of each of the 10 resulting mutants in soluble cell lysates against D- and L-2-chloropropionic acid was assessed. Interestingly, the mutants W34!A, F37!A, and S188!A had diminished activity, suggesting that these residues are functionally relevant. Notably, the D189!N mutant had no activity, which strongly implies that it is a catalytically important residue. Given our data, we propose a dehalogenation mechanism for DehE, which is the same as that suggested for other non-stereospeciﬁc a-haloalkanoic acid dehalogenases. To the best of our knowledge, this is the ﬁrst report detailing a functional aspect for DehE, and our results could help pave the way for the bioengineering of haloalkanoic acid dehalogenases with improved catalytic properties.